Rudists (Bivalvia: Hippuritida) from the Lower Cretaceous Khalsi Formation, Ladakh, India, and their palaeogeographic implications. (April 2023) - Barman, Prasenjit; Swami, Narendra K.; Rao, Xin; Mishra, S.R.; Ibrahim, Mohd; Singh, Shailendra
Abstract: Rudist fauna composed of the Radiolitidae and the Polyconitidae is reported from the Aptian–Albian Khalsi Formation, southern Ladakh, India. The rudists are identified as Auroradiolites gilgitensis, A. biconvexus, Magallanesia rutogensis, and Shajia tibetica . Among them, A. biconvexus and M. rutogensis are described first time in Ladakh. Additionally, two radiolitid specimens reported from the Saltoro Formation of the SSZ in northern Ladakh by Upadhyay (2014), are assigned to A. biconvexus, and one single specimen from Saltoro Formation which was assigned to Horiopleura sp. by Upadhyay (2014), is questionably transferred to S. tibetica in this study. The occurrence of A. gilgitensis in the early Aptian of Ladakh provides evidence for the eastern dispersal pattern of A. gilgitensis during early Aptian. The finding of M. rutogensis in Ladakh fills the geographical gap between the first plagioptychid, early Turonian Plagioptychus haueri in the Mediterranean and the previous westernmost record of M. rutogensis in Lhasa Block, and further strengthens the hypothesis that Plagioptychidae was evolved from Magallanesia or related form. The association of A. biconvexus, A. gilgitensis, and M. canaliculata support the hypothesis of southwest Asian- Pacific province for the palaeobiogeographic linkage of Auroradiolites and Horiopleura haydeni – Praecaprotina – Magallanesia . This study provides additional evidence in favour of the relatively close geographical connection and tectonic equivalence between the Ladakh and Lhasa blocks during the mid-Cretaceous. Meanwhile, it highlights the need for detailed biostratigraphic studies in other microcontinents along the northern margin of the East Tethys, which may provide critical information for their tectonic and palaeogeographic evolution.